Subject-oriented educational robotics applications with Arduino in science teaching: digital dynamometer activity in accordance with 5E instractional model. (18th October 2022) - Koray, Abdullah; Duman, Fikriye Gökçehan
Abstract: The purpose of this article is to design and develop an Arduino-assisted robotic and coding activity in compliance with the 5E instructional model in order to help secondary school students improve their science achievement in the science course. The research was conducted with 5th grade students studying at a private secondary school in Turkey in the spring semester of the 2020–2021 academic year. The implementation of the designed activity was carried out within the scope of the science course with the participation of 20 students. The activity is designed to teach the concept of dynamometer, which is considered within the scope of measuring force in the science course curriculum, in accordance with the 5E instructional model. In this activity, the elongation of the rubber band with a weight attached to the end was measured by a distance sensor, and a dynamometer model was designed by coding. In addition, this activity was presented to the students as one example of solving daily life problems by making use of technology. As a result, the students have the opportunity to explore Arduino-powered robotics and coding applications and integrate these applications into science course.